High Flow Nasal Cannula for Management of Tuberculous ARDS in Immunocompromised – A Vision or an Illusion - Choudhary, Robin; Marwah, Vikas; Singh, Manish; Gupta, Simple (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2021)
Tuberculosis (TB), although commonly thought to be a chronic pulmonary disease, indeed has protean manifestations. One of its varied acute presentations is Tuberculous ARDS, which is a rare but fatal form of TB with mortality reported as high as 69-80%. Here we report a case of sputum smear-positive MDR miliary tuberculosis with tuberculous ARDS in a patient with AIDS managed with HFNC oxygen therapy. Diagnosis of tuberculosis was based on clinical radiological, microbiological and molecular evidence. The diagnosis of ARDS was established as per Berlin definition. The patient was successfully managed with HFNC oxygen therapy along with second line anti tubercular treatment (ATT) and supportive measures.